A 12

012. `*   12

 

 

*   1.4.12 (was 1.4.6). Explain how you found the real solutions of the equation (1-2x)^(1/3) - 1 = 0

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

 Since -1 does not contain the variable to solve for, move it to the right hand side of the equation by adding 1 to both sides. Get rid of the fraction exponent on the lefthand side by raising both sides to the 3 power...((1-2x)^1/2)^3=(1)^3 Factor...(1-2x))=(1)^3 Remove the parentheses around the expression 1-2x...1-2x=(1)^3...1-2x=1. Since 1 does not have the variable to solve for, subtract 1 from boh sides..-2x=-1+ 1..-2x=0...divide x=0/-2..x=0

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Starting with

 

(1-2x)^(1/3)-1=0

add 1 to both sides to get

(1-2x)^(1/3)=1

then raise both sides to the power 3 to get

[(1-2x)^(1/3)]^3 = 1^3.

 

Since [(1-2x)^(1/3)]^3 = (1 - 2x) ^( 1/3 * 3) = (1-2x)^1 = 1 - 2x we have

 

1-2x=1.

 

Adding -1 to both sides we get

-2x=0

so that

x=0.

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 

 

------------------------------------------------

Self-critique Rating: 3 OK

*********************************************

Question: *   1.4.28 (was 1.4.18). Explain how you found the real solutions of the equation sqrt(3x+7) + sqrt(x+2) = 1.

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

 sqrt(3x+7)= -sqrt(x+2) + 1 .

Now we square both sides to get

sqrt(3x+7)^2 =[ -sqrt(x+2) +1]^2.

Expanding the right-hand side using (a+b)^2 = a^2 + 2 a b + b^2 with a = -sqrt(x+2) and b = 1:

3x+7= x+2 - 2sqrt(x+2) +1.

Note that whatever we do we can't avoid that term -2 sqrt(x+2).

 

Simplifying

3x+7= x+ 3 - 2sqrt(x+2)

then adding -(x+3) we have

3x+7-x-3 = -2sqrt(x+2).

Squaring both sides we get

(2x+4)^2 = (-2sqrt(x+2))^2.

 

Note that when you do this step you square away the - sign.  This can result in extraneous solutions.

 

We get

 

4x^2+16x+16= 4(x+2).

Applying the distributive law we have

4x^2+16x+16=4x+8.

Adding -4x - 8 to both sides we obtain

4x^2+12x+8=0.

Factoring 4 we get

4*((x+1)(x+2)=0

and dividing both sides by 4 we have

(x+1)(x+2)=0

Applying the zero principle we end up with

(x+1)(x+2)=0

so that our potential solution set is

x= {-1, -2}.

 

Both of these solutions need to be checked in the original equation sqrt(3x+7)+sqrt(x+2)=1

 

the solution -2 gives us sqrr(1) + sqrt(0) = 1 or 1 + 0 = 1, which is true.

 

x = -1 is an extraneous solution that was introduced in our squaring step.

Thus our only solution is x = -2.

 

 

confidence rating #$&*: 3 OK

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Starting with

 

sqrt(3x+7)+sqrt(x+2)=1

 

we could just square both sides, recalling that (a+b)^2 = a^2 + 2 a b + b^2.

 

This would be valid but instead we will add -sqrt(x+2) to both sides to get a form with a square root on both sides. This choice is arbitrary; it could be done either way. We get

 

sqrt(3x+7)= -sqrt(x+2) + 1 .

Now we square both sides to get

sqrt(3x+7)^2 =[ -sqrt(x+2) +1]^2.

Expanding the right-hand side using (a+b)^2 = a^2 + 2 a b + b^2 with a = -sqrt(x+2) and b = 1:

3x+7= x+2 - 2sqrt(x+2) +1.

Note that whatever we do we can't avoid that term -2 sqrt(x+2).

 

Simplifying

3x+7= x+ 3 - 2sqrt(x+2)

then adding -(x+3) we have

3x+7-x-3 = -2sqrt(x+2).

Squaring both sides we get

(2x+4)^2 = (-2sqrt(x+2))^2.

 

Note that when you do this step you square away the - sign.  This can result in extraneous solutions.

 

We get

 

4x^2+16x+16= 4(x+2).

Applying the distributive law we have

4x^2+16x+16=4x+8.

Adding -4x - 8 to both sides we obtain

4x^2+12x+8=0.

Factoring 4 we get

4*((x+1)(x+2)=0

and dividing both sides by 4 we have

(x+1)(x+2)=0

Applying the zero principle we end up with

(x+1)(x+2)=0

so that our potential solution set is

x= {-1, -2}.

 

Both of these solutions need to be checked in the original equation sqrt(3x+7)+sqrt(x+2)=1

 

As it turns out:

 

the solution -1 gives us sqrt(4) + sqrt(1) = 1 or 2 + 1 = 1, which isn't true,

while

the solution -2 gives us sqrr(1) + sqrt(0) = 1 or 1 + 0 = 1, which is true.

 

x = -1 is an extraneous solution that was introduced in our squaring step.

Thus our only solution is x = -2. **

STUDENT QUESTION

 

I got to the third step but I got confused on what to eliminate or substitute in, looking at the solution, im still a little confused on how it all worked out. U got any suggestions on how to look at it in a better way???

INSTRUCTOR RESPONSE

You're pretty much stuck with this technique and this way of looking at the problem.

It should be pretty clear to you that

(sqrt(x+3))^2 is just x + 3.

Squaring the expression [ -sqrt(x+2) +1] is a little more challenging.

We could use the distributive law:

[ -sqrt(x+2) +1]^2

= [-sqrt(x + 2) + 1 ] * [-sqrt(x + 2) + 1 ]

= -sqrt(x+2) * [-sqrt(x + 2) + 1 ] + 1 * [-sqrt(x + 2) + 1 ]

= -sqrt(x+2) * (-sqrt(x + 2) ) + (-sqrt(x + 2) * 1 + 1 * (-sqrt(x + 2) ) + 1 * 1

= (x + 2) - sqrt(x + 2) - sqrt(x + 2) + 1

= x+2 - 2sqrt(x+2) +1.

Once we get the equation

3x+7= x+2 - 2sqrt(x+2) +1

we see that we still need to 'get to' that x within the square root. To do that we rearrange the equation so that the square root is on one side, all by itself, so we can square it without dragging a lot of other stuff along.

So we do a couple of steps and we get

3x+7-x-3 = -2sqrt(x+2).

If we square both sides of this equation, we get rid of all the square roots and we get x out where we can deal with it.

The details are in the given solution, but we get the equation

4x^2+16x+16= 4(x+2).

This equation now has x^2 and x terms, so we know it's a quadratic, and we rearrange and solve it as such. The details are in the given solution.

COMMON ERROR

 

sqrt(3x+7)^2= (-sqrt(x+2)+1)^2

(3x+7)=(x+2)+1

EXPLANATION

(a + b)^2 = (a + b) * (a + b) = a ( a + b) + b ( a + b) = a * a + a * b + b * a + b * b.

So (a + b)^2 is not equal to a^2 + b^2.

 

Nor is it so that

 

(-sqrt(x+2)+1)^2 is equal to (x+2) + 1.

When you square the right-hand side you can't write it

-sqrt(x+2)+1 ^2

because written this way only the 1 gets squared.

You have to write it

(-sqrt(x+2)+1) ^2,

which means

(-sqrt(x+2) + 1) * (-sqrt(x+2) + 1).

When multiplied out using the distributive law, using the same sequence of steps used above to find (a + b) ( a + b), you should get

 

(x + 2) - 2 sqrt( x + 2) + 1.

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 

 

------------------------------------------------

Self-critique Rating: 3 OK

*********************************************

Question: *   1.4.40 (was 1.4.30). Explain how you found the real solutions of the equation x^(3/4) - 9 x^(1/4) = 0.

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 Find a common factor for each term.

1(x^1/4)^3 minus 9x^1/4=0...Substitute u=x^1/4 and solve for u. u^3-9u=0 where u=x^1/4. Factor out the GCF of u from each term in the polynomial u(u^2)+u(-9)=0. Factor out the GCF of u from u^3-9u...u(u^2-9)=0...The binomial can be factored using the difference of squares formula, because both terms are perfect squares..Where a=u and b=3 u(u-3)(u+3)=0 Set the single term factor on the left hand ide of the equation = to zero … u=0,3,-3 Substitute the x^1/4=u back into the solved equation in order to solve for x...x^1/4=0..Solve equation for x then we put x^1/4=3 then so x=81. X^1/4=-3..x=81...0,81,81

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Here we can factor x^(1/4) from both sides:

 

Starting with

 

x^(3/4) - 9 x^(1/4) = 0

we factor as indicated to get

x^(1/4) ( x^(1/2) - 9) = 0.

Applying the zero principle we get

x^(1/4) = 0 or x^(1/2) - 9 = 0

which gives us

x = 0 or x^(1/2) = 9.

 

Squaring both sides of x^(1/2) = 9 we get x = 81.

 

So our solution set is {0, 81). **

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 

 

------------------------------------------------

Self-critique Rating: 3 OK

*********************************************

Question: *   1.4.46 (was 1.4.36). Explain how you found the real solutions of the equation x^6 - 7 x^3 - 8 =0

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

  a = x^3.

 

Then a^2 = x^6 and the equation x^6 - 7x^3 - 8=0 becomes

 

a^2 - 7 a - 8 = 0.

This factors into

(a-8)(a+1) = 0,

with solutions

a = 8, a = -1.

 

Since a = x^3 the solutions are

 

x^3 = 8 and

x^3 = -1.

 

We solve these equations to get

 

x = 8^(1/3) = 2

and

x = (-1)^(1/3) = -1.

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Let a = x^3.

 

Then a^2 = x^6 and the equation x^6 - 7x^3 - 8=0 becomes

 

a^2 - 7 a - 8 = 0.

This factors into

(a-8)(a+1) = 0,

with solutions

a = 8, a = -1.

 

Since a = x^3 the solutions are

 

x^3 = 8 and

x^3 = -1.

 

We solve these equations to get

 

x = 8^(1/3) = 2

and

x = (-1)^(1/3) = -1.

STUDENT QUESTION

 

I am confused as to why you substituted the a. I know how to do this on the calculator by using y = and 2nd graph to get the solution (-1, 2)

INSTRUCTOR RESPONSE

If you substitute a for x^3, then you end up with a quadratic equation that can be easily factored.

If a = x^3, then x^6 = a^2 so the equation becomes

a^2 - 7 a - 8 = 0.

We factor this and find that a can be either 8 or -1.

So x^3 can be either 8 or -1.

Thus x can be either 2 or -1.

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 

 

------------------------------------------------

Self-critique Rating: 3 OK

*********************************************

Question: *   1.4.64 (was 1.4.54). Explain how you found the real solutions of the equation x^2 - 3 x - sqrt(x^2 - 3x) = 2.

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

 Alright u = sqrt(x^2 - 3x).

 

Then u^2 = x^2 - 3x, and the equation is

 

u^2 - u = 2.

 

 

u^2 - u - 2 = 0.

 

(u-2)(u+1) = 0.

 

Solutions are u = 2, u = -1.

 

sqrt(x^2 - 3 x) = 2

sqrt(x^2 - 3 x) = -1.

 

sqrt(x^2 - 3x) = 2

x^2 - 3x = 4.

x^2 - 3x - 4 = 0

(x-4)(x+1) = 0

x = 4 or x = -1.

 

 

confidence rating #$&*: 3 OK

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Let u = sqrt(x^2 - 3x).

 

Then u^2 = x^2 - 3x, and the equation is

 

u^2 - u = 2.

 

Rearrange to get

 

u^2 - u - 2 = 0.

 

Factor to get

 

(u-2)(u+1) = 0.

 

Solutions are u = 2, u = -1.

 

Substituting x^2 - 3x back in for u we get

 

sqrt(x^2 - 3 x) = 2

and

sqrt(x^2 - 3 x) = -1.

 

The second is impossible since sqrt can't be negative.

 

The first gives us

 

sqrt(x^2 - 3x) = 2

so

x^2 - 3x = 4.

Rearranging we have

x^2 - 3x - 4 = 0

so that

(x-4)(x+1) = 0

and

x = 4 or x = -1.

 

STUDENT QUESTION

 

I got stuck on this part u=(-sqrt2+-sqrt10)/2, but after I looked at the solution, it made a little more sense to me, but im not real confident. Got any suggestions on how to approach it in a different way???

INSTRUCTOR RESPONSE

Plugging into the quadratic formula we get

u=(-sqrt2+-sqrt10)/2,

meaning u can take one of the two values

u=(-sqrt2+sqrt10)/2

or

u=(-sqrt2-sqrt10)/2.

These quantities are just plain old numbers, which you could evaluate (up to some roundoff) on your calculator.

The first possible value of u is about equal to about .874.

The second possible value of u is negative.

Now u stands for x^2, so we ignore the negative value of u (this since x^2 can't be negative).

So we're left with

x^2 = u = .874.

So x = +- sqrt(.874), giving us the values of x in the given solution.

STUDENT QUESTION

 

I still do not understand using u. I can do it from the 2nd step. Problem: u^2 - u - 2 = 0. Factor: (u-2)(u + 1) = 0. You get u = 2, -1. You will solve x^2 - 3x -4. Factor will be (x - 4)(x + 1) = 0. Solutions are 4, -1.

INSTRUCTOR RESPONSE

The left-hand side consists of

x^2 - 3x

and

the square root of x^2 - 3x.

So instead of

x^2 - 3 x - sqrt(x^2 - 3x)

we write the left-hand side as

u - sqrt(u),

which is easier to deal with.

We solve for u, then come back and figure out what value(s) of x give us our values of u.

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): 3 OK

 

 

------------------------------------------------

Self-critique Rating:

*********************************************

Question: *   1.4.92 \ 90 (was 1.4.66). Explain how you found the real solutions of the equation x^4 + sqrt(2) x^2 - 2 = 0.

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 Well x^4 plus radical2x^2 minus 2 =0. We move the term after the radical to the front of the radical (radical 2x^2) x^4 plus times x^2 radical 2 minus 2= 0. Multiply x^2 to get x^2 x^4 plus times x^2 radical 2 minus 2= 0

 

 

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* *  Starting with

 

x^4+ sqrt(2)x^2-2=0

 

we let u=x^2 so that u^2 = x^4 giving us the equation

 

u^2 + sqrt(2)u-2=0

 

Using the quadratic formula

 

u=(-sqrt2 +- sqrt(2-(-8))/2

so

u=(-sqrt2+-sqrt10)/2

 

Note that u = (-sqrt(2) - sqrt(10) ) / 2 is negative, and u = ( -sqrt(2) + sqrt(10) ) / 2 is positive.

 

u = x^2, so u can only be positive. Thus the only solutions are the solutions to the equation come from

 

x^2 = ( -sqrt(2) + sqrt(10) ) / 2.

The solutions are

x = sqrt( ( -sqrt(2) + sqrt(10) ) / 2 )

and

x = -sqrt( ( -sqrt(2) + sqrt(10) ) / 2 ).

 

Approximations to three significant figures are

 

x = .935

and

x = -.935.

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 

 

------------------------------------------------

Self-critique Rating: 3 OK

 

Add comments on any surprises or insights you experienced as a result of this assignment.

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

 

Add comments on any surprises or insights you experienced as a result of this assignment.

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#Good responses. Let me know if you have questions. &#